Geografia i skala produkcji XIX-wiecznych modlitewników na Kresach Wschodnich - Ratajczak, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Eastern Borderlands, that is, the territory belonging to the former Second Polish Republic, not only boast a fascinating history but also have exerted a noticeable influence on the Polish culture in its broad sense. Situated to the east of 19th-century Polish Kingdom, that is, between the Bug and the Niemen as well as the Dźwina and the Dniepr, which after WW II was expanded by the former Red Ruthenia or Eastern Galicia with Lviv as its leading spot, this territory played an important role in the history of Polish book and its printing centers. The present paper focuses on the effects of these centers` activity with respect to 19th-century volume and geography of the production of borderland utility and religious prints.
Keywords: modlitewniki polskie; religijna literatura użytkowa; Kresy Wschodnie; Polish prayer books; applied religious literature; Eastern Borderlands; 19 w.; 19th century